Gestores escolares e projeto político-pedagógico: desafios e perspectivas para a educação de jovens e adultos - Cristiane Fernanda Xavier (2008)
The purpose of this research is to investigate the role of educational managers in a political and pedagogical project focused on the young and adult education (EJA) and the implications of teachers formation in relation to their practice from 2006 to 2008. In doing so, this study explores the aspects related to educational managers behavior towards the building and implementation of EJA project through the identification of the challenges, dilemmas and management strategies these professionals have developed, within the context of the so called Escola Plural of the municipal sector in Belo Horizonte, Minas Gerais State. The methodology applied consists of a semi-open questionnaire designed to characterize the research subjects belonging to two municipal schools of Belo Horizonte in which EJA classes are being held; moreover, observation and analysis of the political pedagogical projects of schools where the educational managers work as well as interviews have been adopted. The study is rooted in the idea that a political pedagogical project is regarded as an otherness space which provides relevant and meaningful learning experiences to the educational processes of EJA, besides being a space that keeps both emancipatory and regulatory potentialities. Confirming the principles of Popular Education as fundamentals required by the educational practices developed in EJA, this research keeps a dialogue with the teaching formation as far as demands and perspectives for EJA are concerned. It points out the role of educational managers as individuals who are able to potentialize meaningful educational experiences in the area, encourage the interlocution of EJA with is historical constitutional roots and widen the meanings of both the school and the schooling formation of EJA students and teachers. Finally, it presents evidences that partnerships between schools and universities for the construction of emancipatory educational practices within EJA can be viewed as a possible management strategy.